Heavy Metal Contaminated Food Crops Irrigated with Wastewater in Peri Urban Areas, Zambia - Kapungwe, Evaristo Mwaba (Scientific Research, 2013)
Studies on peri urban farming in Zambia have not adequately tackled the issues pertaining to heavy metal contaminated wastewater irrigation farming. The study investigated heavy metal contamination of water, soils and crops at two peri urban areas in Zambia. Two study sites were New Farm Extension in Mufulira Town in the Copperbelt Province and Chilumba Gardens in Kafue Town in Lusaka Province. The heavy metals investigated were lead, copper, cobalt, nickel and chromium. These heavy metals were found to be higher than acceptable limits in wastewater used to irrigate crops and there are potential human health risks associated with consumption of heavy metal contaminated food crops which have implications on the livelihoods of people. Samples of water, soil and crops were collected and analysed for lead (Pb), copper (Cu), chromium (Cr), cobalt (Co) and nickel (Ni) using the Atomic Absorption Spectrometer (AAS). The data on heavy metals was analysed using mean, standard error and T-test. The results indicated that the levels of heavy metals in wastewater, soil and food crops were above acceptable limits at two study sites. It can be concluded that there was heavy metal contamination of wastewater, soil and food crops at the two peri-urban areas in Zambia. The study highlighted the actual levels of heavy metal contaminant uptake in food crops consumed by the peri urban population. The information from this study can be used by the relevant authorities to develop appropriate measures for monitoring and control of heavy metal contamination in wastewater irrigation farming systems in peri urban areas in Zambia.
Keywords: Heavy Metal Contamination; Wastewater; Soils; Food Crops; Irrigation Farming; Peri Urban Areas; Zambia